Inhibition of BET Protein Function Suppressed the Overactivation of the Canonical NF-κB Signaling Pathway in 6-OHDA-Lesioned Rat Model of Levodopa-Induced Dyskinesia - Wan, Ying; Han, Li; Rong, Lu; Yang, Shuyuan; Song, Lu; Wu, Na; Liu, Zhenguo; Gan, Jing (Frontiers in Neuroscience, 2022)
Backgrounds: Neuroinflammation was involved in the mechanisms of levodopa induced dyskinesia (LID). The canonical NF-κB activation signaling pathway played a critical role in the neuroinflammation development and BET proteins mediated NF-κB mediated neuroinflammation. Inhibition of BET proteins function was reported to alleviate LID, however, it remains unknown about its association with the canonical NF-κB signaling pathway in the 6-OHDA lesioned striatum of LID rat model. Accordingly, we would identify the status of the canonical NF-kB signaling pathway in the 6-OHDA-lesioned striatum of LID rat model and whether the anti-dyskinetic effect of the BET inhibitor JQ1 was associated with its suppression on NF-kB mediated neuroinflammation. Methods: 6-OHDA PD rat models were treated with either L-dopa plus JQ 1 or L-dopa alone. L-dopa treatment lasted for two weeks, the JQ1 treatment lasted for three weeks and was initiated a week prior to L -dopa treatment. As a control, the sham rats were treated with JQ1 or veh for three weeks. ALO AIM assessment and Cylinder test were performed during the treatment. Glia activation markers, the pro-inflammatory substances and the critical proteins in the canonical NF-kB signaling pathway were tested in the lesioned striatum after the final treatment. Results: JQ1 effectively alleviated LID without influencing motor improvement. In the lesioned striatum, L-dopa triggered an overactivation of the canonical NF-kB signaling pathway, with an increase in the phospho-IKKα/β，phospho- IκBα，NF-kB nuclear translocation and its phosphorylation at Ser536 and Ser 276 sites (p<0.01 vs Sham group). L-dopa induced an overexpression of the pro-inflammatory substances of TNF-α, IL-1β, IL-6 and iNOS, the glia activation maker CD68 and GFAP. All the molecular changes were greatly inhibited by JQ1.Conclusions: L-dopa triggered an overactivation of the canonical NF-κB signaling pathway, leading to an enhanced neuroinflammation response in the 6-OHDA lesioned striatum of LID rat models. Inhibition of BET protein function significantly suppressed the activation of the canonical NF-κB signaling pathway in the striatum, alleviating the neuroinflammation response and the severity of LID.